Review of progress to date and outline of plans for developements up to 1977 - Henry, Harry; Wills, Gordon (Cranfield School of Management, 1974)
This report seeks to summarize the ground covered so far by the MCRU since it began work in 1968. In particular, the Report reviews progress in the major investigation sponsored by 22 Companies into the "Methods of Measuring Advertising Effectiveness". Its second purpose is to pose questions and formulate an outline plan of the future development currently envisaged by Cranfield for its MCRU. Sponsor companies on the MCRU's main project, and other associates, are invited to submit their comments and reactions on February 28, 1974. Following discussion then, our formal plan for the next three years will be delineated.